Hypothyroidism in pregnancy: the scourge of the hills - Chakravarty, Rony; Bajaj, Varun; Nair, Rajesh; Gupta, Ramkumar; Rao, Pankaj P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypothyroidism is a causal agent sub serving a multitude of complications in pregnancy. There is a lot of controversy regarding universal screening for thyroid abnormalities during pregnancy. An attempt was made to ascertain the incidence of hypothyroidism during pregnancy in a peripheral hospital. Methods: All patients reporting to ANC OPD were subjected to thyroid profile and results tabulated as per ATA guidelines 2017. Patients with clinical hypothyroidism were followed up with treatment to look for condition related complications if any. Complications despite treatment were noted and included only after ruling out masquerading mimickers or co existent conditions. Results: An incidence of 14.46% per two years was detected with hypothyroidism. Conclusions: The need for universal screening for hypothyroidism is inescapable particularly in hilly terrain.